Analisis Pengelolaan Keuangan Dana Desa Dalam Menunjang Pembangunan Kampung Tahima Soroma Distrik Jayapura Selatan Kota Jayapura Papua - Koroh, Aprilianda Alfa Aditya Juan; Falah, Syaikul; Mudassir, Annisa (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2025)
This study aims to analyze the financial management of Village Funds to support physical and non-physical development in Tahima Soroma Village, South Jayapura District, Jayapura City, Papua. The method used was a descriptive qualitative approach with in-depth interviews, observation, and documentation studies. Data were analyzed using NVivo 12 software. The results indicate that Village Fund management has been implemented in accordance with Home Affairs Ministerial Regulation No. 20 of 2018, but there are still obstacles related to community participation and the capacity of village officials. In conclusion, the effectiveness of fund management is largely determined by transparency, accountability, and active community participation. This implies the need for training for village officials and the application of information technology in financial management.